(untitled) (Journal of Universal Science Research, 2024)
The President of Uzbekistan, Sh. M. Mirziyoyev, and the government have paid great attention to Olympic sports, including athletics. The Law on "Physical Education and Sports" of the Republic of Uzbekistan (revised in 2015), Presidential Decree No. PQ-5368 on "Measures to Radically Improve the State Management System in the Field of Physical Education and Sports," and Decree No. PQ-3031 on "Measures to Further Develop Physical Education and Mass Sports" are clear examples of this. The role of high sports achievements, the intensifying competition at international competitions, and the generational change of athletes in national teams highlight the need for scientifically grounded systems for selecting and training promising young athletes. In the selection of children for sports, along with other indicators, determining their individual physical readiness, technical training indicators, and personal qualities is essential. The need for scientific research on effective approaches and methods to improve the process of selecting and identifying talented young sprinters defines the relevance of this work.